Detection of bovine viral diarrhoea virus (BVDV) in peripheral blood mononuclear cells (PBMCs) of BVDV antibody positive Indian cattle following mitogen stimulation - GUPTA, V; MISHRA, N; RAJUKUMAR, K; BEHERA, S P; DUBEY, P (The Indian Journal of Animal Sciences, 2014)
The aim of the present study was possible detection of BVDV in peripheral blood mononuclear cells (PBMCs) of antibody positive naturally infected Indian cattle following phytohaemagglutinin A (PHA) stimulation. Of 250 serum samples from cattle in organized dairy firms in India tested by virus neutralization test (VNT), 93 cattle (37.2%) were found positive for BVDV neutralizing antibodies. The PBMCs from BVDV-immune cattle were stimulated with 5µg/ml of PHA for 72 h prior to BVDV RNA detection by RT-PCR or infectious virus detection by virus isolation. Of the 93 BVDV immune field cattle tested positive, BVDV RNA was detected only in PHA stimulated PBMCs of 3 cattle, while no infectious BVDV could be detected by virus isolation. This is for the first time, that BVDV RNA was detected following mitogen (PHA) stimulation of PBMCs in BVDV antibody positive Indian cattle.